PAPEL DA OSTEOCALCINA E DO SILENCIAMENTO DE APOE COMO MARCADORES DE RISCO DE AGRAVAMENTO DE DOENÇAS METABÓLICAS ASSOCIADAS À MENOPAUSA EM MODELO DE ESTUDO EM MURINOS - Santana, Higor Scardini (2020)
Menopause is characterized by decreased activity of the ovaries, which occurs gradually and, consequently, leads to a reduction in the production of female sex hormones. Estrogen (E2) influences the most diverse phenomena in the body and, therefore, its a